2005
DOI: 10.1007/978-3-540-30578-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Agent–Oriented Software Methodologies – Examination of the Gap Between Modeling and Platform

Abstract: More and more effort is made to provide methodologies for the development of agent-based systems. Awareness has grown that these are necessary to develop high quality agent systems. In recent years a number of proposals has been given. Based on our experiences we argue that a complete evaluation of methodologies cannot be done without considering target platforms, because the differences between available implementations are too fundamental to be ignored. In order to conduct a suitable comparison we present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…Then, the evaluation framework, which is built, which consists of properties, attributes and measures. Measures used here to evaluate OOSE methodologies are based on current works and other works performed on agent-oriented methodologies [19][20][21][22]. The evaluation was focused on the technical properties of the methodologies.…”
Section: Criteria and Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the evaluation framework, which is built, which consists of properties, attributes and measures. Measures used here to evaluate OOSE methodologies are based on current works and other works performed on agent-oriented methodologies [19][20][21][22]. The evaluation was focused on the technical properties of the methodologies.…”
Section: Criteria and Evaluation Methodsmentioning
confidence: 99%
“…These models have various aspects, but are not complete alone, so by putting them together, a complete and understandable view of the system will be achieved. In choosing models of ARA methodology, noted earlier, a complete evaluation frame is used and covers four main areas of agent-oriented software engineering such as [19][20][21][22] concepts, modeling language, process and activism. According to this frame and its parameters, the support of each methodology is evaluated and experts investigated the actor, capacity and programmer proposed models.…”
Section: Introduction the Methodology Of Aramentioning
confidence: 99%
“…An example of these proposals is Tropos [8], an agent-oriented software development methodology. The contribution of Tropos at the requirements stage and in agent-oriented design has been acknowledged by different comparative studies [21][22][23]. Also relevant is URN [24], an i* variation which has been added as part of the industrial Telecommunications Standard Z.151 [25] for systems specification.…”
Section: The I* Framework and Its Variationsmentioning
confidence: 99%
“…TAOM also uses Eclipse, but it does not appear to support cross checking or hierarchical views. The JACK Design Environment (JDE) 10 is also related to our work, since it provides design diagrams. However, the JDE does not support system specification activities or high level design.…”
Section: Discussionmentioning
confidence: 99%
“…In its current state, the tool provides the system developer with a graphical user interface that supports the development of the various artefacts within the Prometheus methodology and assists in * Authors listed alphabetically maintaining a consistent design by providing cross checking between the various diagrams, automatic propagation of design elements when possible and appropriate, and name lookup assistance. The file produced by the tool can be transformed into an agent programming language (work has been reported that transforms this output file into a Jadex agent definition file [10]). The current version of PDT is Java based and hence is platform independent.…”
Section: Introductionmentioning
confidence: 99%